Sperm cryopreservation for impaired spermatogenesis - G Hughes; S Martins da Silva (Bioscientifica, 2023)
Sperm cryopreservation for men with severely impaired spermatogenesis is one of the commonest reasons for short-term sperm storage, usually in advance of fertility treatment. Cryopreservation is generally very effective, although not all spermatozoa survive the process of freezing and thawing. This review considers various aspects of freezing sperm, including an overview of methods, appropriate use of cryoprotectants and practical considerations, as well as oxidative stress and mechanisms of cell cryodamage.